Evaluation of quality of the family health strategy in the Federal District - Helena Eri Shimizu; Maíra Catharina Ramos (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Aim: To evaluate quality of the Family Health Strategy (FHS) in the National Program for Improving Access and Quality of Primary Care in the Federal District (FD) from the perspective of users. Methods: Evaluative research carried out in 25 basic health units of the Federal District through a validated questionnaire assessing the following dimensions: access, gateway, bond, service range, coordination, family focus, community orientation, and health professionals. Results: Service provision, qualification of professionals, quality of professional-user relationship, and continuity of care were the best evaluated dimensions, while family approach, community approach, and access were the worst. Access to the FHS was found to be compromised, besides failing to establish itself as gateway to the FD health system. Conclusion: When they can access the local system, FD users do enjoy several services, but access is still a barrier, mainly because the very system is not prepared to meet users' needs/preferences. The dimensions regarding family focus and community orientation are precarious, which reveals the need for reflection on the care model adopted in the Federal District.